1970
DOI: 10.1163/187529270x00504
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Some Environmental and Cultural Conditions On Rearing Populations of Xiphinema and Longidorus1)

Abstract: Trials were carried out with hand-picked populations of Xiphinema spp. and Longidorus spp. to determine the effect of different environmental and cultural conditions on the nematode multiplication rate. Using Longidorus africanus as a test organism, a four-fold population increase within 5 months was recorded in polyethylene bottles as compared with that in clay pots; population build-up of L. africanus, Xiphinema brevicolle, X. diversicaudatum, X. index, and X. italiae in polyethylene bottles was quicker in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, significant development of X. californicum populations did not affect plant growth [114]. In fact, DNs are usually difficult to rear in controlled conditions because of their susceptibility to moisture and temperature variations [122]. That could explain failures in pathogenicity experiments [53].…”
Section: Xiphinema Spp (Dagger Nematodes)mentioning
confidence: 99%
“…However, significant development of X. californicum populations did not affect plant growth [114]. In fact, DNs are usually difficult to rear in controlled conditions because of their susceptibility to moisture and temperature variations [122]. That could explain failures in pathogenicity experiments [53].…”
Section: Xiphinema Spp (Dagger Nematodes)mentioning
confidence: 99%
“…Earlier studies showed substantial variations in reproduction rates and life cycle stages under greenhouse conditions (Cohn & Mordechai, 1970;Coiro et al, 1990); X. index reproduced faster in non-clay soils under these conditions (Coiro et al, 1987). Fine sand and sandy loam soils with a soil moisture content of 10 to 15% induced higher reproduction results than coarse sand (Sultan & Ferris, 1991).…”
Section: Range Habitat Biology and Culturing Of Xiphinema Indexmentioning
confidence: 95%